منهج دراسة علوم البلاغة لمتعلمي اللغة العربية الناطقين بلغات أخرى - إبراهيم علي كياري (Prosiding Konferensi Nasional Bahasa Arab, 2020)
ملخص البحثعلوم البلاغة من أهم علوم اللغة العربية تعلقا بالقرآن الكريم، وهي المدخل الطبيعي لإتقان تفسير القرآن الكريم، وعلى الرغم من أهميتها إلا أنها لا يلقى الاهتمام في تدريسها لمتعلمي اللغة العربية الناطقين بلغات أخرى، ومن هنا جاءت فكرة العنوان: "منهج تدريس علوم البلاغة لمتعلمي اللغة العربية الناطقين بلغات أخرى" لذكر المنهج المناسب في تدريسها. وتتمثل مشكلة البحث في ندرة تصميم منهج تدريس العلوم العربية، وبالأخص علم البلاغة بأنواعها الثلاثة البيان، والبديع، والمعاني. واتبع الباحث في دراسته المنهج الوصفي التحليلي. وتم التوصّل إلى النتائج أهمها: تدريس هذا الفن بطريقة السهولة ثم شبه السهولة ثم الصعوبة، وذلك أن يبدأ الطالب دراسة علم البديع أولا ثم المعاني ثانيا والبيان ثالثا.الكلمات الرئيسية: منهج دراسة؛ البلاغة؛ متعلمي اللغة العربية الناطقين بلغات أخرىAbstractRhetoric is one of the most important science of the Arabic language related to the Holy Qur'an, and it is the natural gateway to master the interpretation of the Holy Qur'an, and despite its importance, it does not receive attention in its teaching to leaners of the Arabic language, especially for non-Arab children, hence the idea of research: The curriculum of  teaching rhetoric to Arabic language learners Non- Arabic speakers, to mention the appropriate method in its teaching. The research problem is the scarcity of designing the curriculum for teaching Arabic sciences, especially the science of rhetoric of its three types, statement, buddy, and meanings. The researcher followed the descriptive analytical method in his study. The most important results were reached: Teaching this art in a manner that is easy, then almost easy, then difficult, and that the student begins studying the science of buaiy first, then the meaning second, and then the statement last.Keywords: Learning Method; Rhetoric; Arabic Learners; Non-Arabic Speaker